1) 3x - 12 = 0
<=> 3x = 12
<=> x = 4
2) (x-2)(2x+3) = 0
<=> x-2 = 0 và 2x + 3 =0
<=> x =2 và x = -3/2
3) \(\dfrac{x-2}{x+2}-\dfrac{3}{x-2}=\dfrac{2\left(x-11\right)}{x^2-4}\)
\(\Leftrightarrow\left(x-2\right)^2-3\left(x+2\right)=2\left(x-11\right)\)
<=> \(x^2-4x+4-3x-6=2x-22\)
\(\Leftrightarrow x^2-4x-3x-2x=-4+6-22\)
\(\Leftrightarrow x^2-9x=-20\)
\(\Leftrightarrow x\left(x-9\right)=-20\)
\(\Leftrightarrow x=-20\) và \(x=-11\)
4) \(\left|x+5\right|=3x+1\)
\(\Leftrightarrow\left[{}\begin{matrix}x-5=3x+1\\-x+5=3x+1\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3x=5+1\\-x-3x=-5+1\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}-2x=6\\-4x=4\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=-1\end{matrix}\right.\)